KAJIAN ANTROPOLINGUSITIK TRADISI OJHUNG DI DESA BUGEMAN KECAMATAN KENDIT KABUPATEN SITUBONDO - Rahmatullah, Muhammad Firdaus; Sulistyowati, Heny; Sulaeman, Agus (Hiski Malang, 2023)
This study seeks to identify the ojhung tradition in Bugeman Village, Kendit District, Situbondo Regency, based on anthropological elements. The emphasis of this research is based on the study of language, culture, and the values ​​contained therein. This study was designed using a qualitative approach using ethnographic methods with an anthropolinguistic design. Sources of research data are informants as resource persons as many as three people who are classified based on professional criteria and social status. The data of this research are the oral utterances of the informants as they are which inform the ojhung tradition. The collection of research data was carried out by observation and interview techniques. The results of this study are that ojhung is a procession for the people of Bugeman Village to ask for safety, rain, abundant harvests, and repel reinforcements. The Bugeman community is an agrarian society with the Madurese language as their daily language so that the term ojhung itself is a term derived from the Madurese language. In addition, there are values ​​related to culture, namely values ​​related to God, values ​​related to and oriented to nature, values ​​related to and oriented to time, values ​​related to and activity oriented, and values ​​related to and oriented to human relations.